Development of an Intelligent System for Recommending and Ordering Healthy Food Menus via a Digital Platform - หล่อนิล , ณัฐพล; เลาะเลิศสุข , วุฒิพงศ์; พัญชยชานันท์ , พัญชนัฐ; เพชรรัตน์ , ธานี; เกตุษา , ชุติมา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The research titled “Development of an Intelligent System for Recommending and Ordering Healthy Food Menus through a Digital Platform” aims to develop a system that facilitates food selection and ordering while providing detailed nutritional information for each menu item. The system is designed to encourage consumers to choose healthier food options and to improve the efficiency of restaurant management.            The developed system is a web-based platform that allows users to access the menu by scanning a QR Code using their smartphones. Users can view food menus, check nutritional information, and place orders directly through the system. The system consists of two main components: the user system and the administrator system. The user system allows customers to browse menus, view nutritional details, and order food. The administrator system allows staff to manage menu categories, add or edit menu items and images, manage nutritional information, and monitor orders and sales statistics.            The results of the system development show that the system helps increase convenience and speed in ordering food, reduces errors in order processing, and enables consumers to easily access nutritional information. Consequently, it improves service efficiency within restaurants and supports healthier food choices for consumers.